Health-Related Quality of Life in Cushing Disease: Discrepancy Between Parent and Child Reports - Keil, Margaret F (J Endocr Soc, 2021)
Background: Previously we reported impairment in quality of life (QoL) measures in children with Cushing disease (CD) by parent proxy; however, little is known about QoL measures from the affected child’s perspective. Method: Prospective study of 48 (26 females, Age:11.5±3.0 yr.) children diagnosed with CD. Prior to treatment, the Child Health Questionnaire (CHQ) was used to assess QoL by parent (proxy) and child report. Results: In children with active CD, there was a discrepancy between parent and child responses for mental health and self-esteem subscales. Child responses were significantly lower than parent responses (lower scores indicate poorer function) for mental health (56 ± 2 vs. 67 ± 2, p&lt0.001) and self-esteem (32.8 ±3 vs. 60.5 ±3, p&lt0.001). No significant differences were found between parent vs.child report for other subscale scores of the CHQ. Conclusion: This is the first study to compare child vs. parent report of health-related quality of life children with active CD. Parent reports underestimated the impact of CD on quality of life measures for mental health and self-esteem. It is important for clinicians to obtain information about health-related quality of life from the child’s perspective in order to guide management and take precautionary measures to alleviate negative outcomes.